Sinus irrigation penetration after balloon sinuplasty vs functional endoscopic sinus surgery in a cadaveric model. Issue 9 (23rd July 2019) - Gantz, Oliver; Danielian, Arman; Yu, Alison; Ference, Elisabeth H.; Kuan, Edward C.; Wrobel, Bozena
Abstract : Background: Nasal irrigation is a cornerstone of treatment for chronic rhinosinusitis. The purpose of this study was to quantify irrigation penetration to the sinuses following balloon sinuplasty and functional endoscopic sinus surgery (FESS). Methods: Balloon sinuplasty followed by FESS was performed on 4 cadaver heads. Using a high‐volume, high‐flow bottle, each head was irrigated with fluorescein‐dyed water prior to and following each procedure, and recorded by rigid endoscopy through trephinations. Three blinded, fellowship‐trained rhinologists reviewed videos and scored the extent of staining (using an accepted scale of 0 to 3) for each site. Results: The mean score prior to any procedure was maxillary sinus 1.67, frontal sinus 1.29, and nasal cavity 1.71. After balloon sinuplasty the mean was maxillary 2.25, frontal 2.04, and nasal cavity 2.17. After FESS the mean was maxillary 2.75, frontal 2.08, and nasal cavity 2.63. There was a statistically significant increase for both maxillary ( p = 0.005) and frontal sinuses ( p = 0.006) following balloon sinuplasty. There was a statistically significant increase following FESS compared to balloon for the maxillary sinus ( p = 0.003), but not the frontal sinus ( p = 0.96). Interrater reliability was good, with Cronbach's alpha of 0.85. Conclusion: Irrigation improved in all sinuses following balloon sinuplasty and FESS. There was further improvement to the maxillary sinus after FESS; however, there was no difference in irrigation to the frontal sinuses following FESS compared to balloon sinuplasty. Extended frontal sinus approaches such as the Modified Lothrop procedure should be considered if more extensive access for irrigation is required.